Medieval philosophy - Dyke, Christina van; Arlig, Andrew W. (Critical concepts in philosophy, 2020)
volume 1. Mind, logic and language -- volume 2: Metaphysics and epistemology -- volume 3: Natural science and philosophical theology -- volume 4: Ethics and moral psychology, and social and political philosophy